An Experimental Fishing Operation of Collapsible Trap for Capture of Coral Fish - Barbara Grace Hutubessy; Jacobus Wilson Mosse (Jurnal Perikanan Universitas Gadjah Mada, 2007)
The aim of this research was to know the effectiveness of the trap which was modified and redesigned from its original. The research was conducted in the water of Baa, Rotendao district, East Nusa Tenggara Province. The trap was operated for 3 months started from August to November 2004 by using three types of baits. Fishes were collected from the trap every 2-3 days immersion by pulling up the trap on board. There were 69 individuals fishes in one trap representing 11 families and 15 species. Most fish species were highly economic values and was dominated by snappers (Lutjanidae) and groupers (Serranidae). The fish size were ranging from 17 to 29 cm of tolat lenght (TL). There was no significant difference between bait used on the catch (p>0.05) suggesting that bait may not be required anymore on this specific reef fishing methods. It is realized that further studies may be required, however in the mean time, this gear may provide an alternative method for small scale reef fishing.